MORPHO-TEXTURAL AND FLUORESCENCE STUDIES ON SIO₂ AND SIO₂@Ce³⁺ - PICIORUȘ, Elena-Mirela; IANĂȘI, Cătălin; NICOLA, Roxana; SFÎRLOAGĂ, Paula; SVERA, Paul; PUTZ, Ana-Maria (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Spherical silica xerogels were synthesized by Stöber route using tetra-ethyl-orthosilicate (TEOS) in order to obtain good properties for opto-electronic and catalytic applications. The reactants mole ratio was n TEOS: H2O: ETOH: NH3 (where n = 0.098 ÷ 0.26: 0.45: 0.789: 0.06). To study these properties, we know from literature, that nanoparticles under 100 nm show unique electrical, mechanical and optical properties. We have choosen the optimum sample, with the smaller surface area and particles size of 91 nm. To improve the optical properties, this sample was further doped with 0.1% Ce3+. The obtained xerogel was thermally treated at 300, 600 and 900 oC. The changes in properties were put in evidence by morpho-textural (N2 adsorption–desorption isotherms and SEM images) and optical measurements (FT-IR, Fluorescence and Raman spectra’s).